CAPPS: Congestion-aware payment and punishment scheme to stimulate selfish nodes in IoT-based VDTNs. - Ghani Ur Rehman; Ali Daud; Omar Ibrahim Aboulola; Bader Alshemaimri; Raed Alsini; Sajid Ullah Khan (PLoS ONE)
The Internet of Things (IoT) is facilitating the connection, identification, sensing, and analysis capabilities of digital devices; enabling them to perform tasks over the internet. Among various IoT applications, Vehicle Delay-Tolerant Networks (VDTNs) stand out, particularly in densely populated cities and rural areas with poor connectivity, where frequent network partitioning, unpredictable connections, and significant delays are common due to node selfishness. Where VDTNs offer promising solutions for such environments, they face challenges like congestion and selfish behavior due to big data traffic and limited resources. Existing systems aiming to mitigate selfishness often exacerbate congestion issues, necessitating a solution to address both concerns effectively. This article proposes the Congestion Aware Payment and Punishment Scheme (CAPPS) to address this issue. It incentivizes cooperation among vehicles and discourages selfish behavior by monitoring nodes. It achieves this by punishing nodes that intentionally discard messages and rewarding those successfully forwarding them. Additionally, CAPPS employs a load-sharing scheme to efficiently manage congestion, routing messages to less congested nodes instead of dropping them. The simulation results show the efficiency of the proposed approach over existing schemes, demonstrating enhanced performance. It improved the packet delivery ratio by around 24%, delivery delay by about 15%, and energy consumption by roughly 13%.